Strengthening Tax Capacity and Bookkeeping Governance in Leather Craft MSMEs - Hunik Sri Runing Sawitri; Asri Laksmi Riani; Salamah Wahyuni; Anastasia Riani Suprapti; Suryandari Istiqomah; Intan Novela Qurratul Aini; Mugi Harsono (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
The Leather Craft MSME Group in Mojopurna Village, Magetan, is a community service partner fostered by the Creative Economy Research Group at the Faculty of Economics and Business, Universitas Sebelas Maret (FEB UNS). To date, the group has encountered several challenges, including low tax awareness among MSMEs and limited product differentiation. The low level of tax compliance is primarily caused by the owners’ limited knowledge and capability in understanding tax regulations and practices, ranging from taxpayer identification number (NPWP) registration to tax reporting and payment procedures. In addition, product innovation development has remained limited because most production activities are based solely on customer orders, coupled with reluctance to develop new models due to risk considerations and the need for new equipment. Consequently, the competitiveness of the leather craft MSMEs in Mojopurna Village, Magetan, has not yet reached its optimal level.  This community service program aims to improve MSME tax literacy and compliance through taxation training. The training activities included the delivery of taxation materials, tax calculation practices, and mentoring sessions. Furthermore, the provision of assistance with production equipment represents a commitment to supporting product innovation among MSMEs. The program's results indicate improved tax literacy, particularly in understanding the types and calculation methods of the MSME Final Income Tax (PPh Final). In addition, production facility support, in the form of a flat heat press machine, contributed to product innovation and enhanced the business capacity of the partner MSMEs through product diversification in accordance with market demand.